Electrodeposition of Platinum Black on Brass - Gustavo A. Maldonado Bautista; Víctor E. Reyes Cruz; Felipe M. Galleguillos Madrid; Jose A. Cobos Murcia; Gustavo Urbano Reyes; Miguel Pérez Labra; Carlos Portillo (Surfaces, 2025)
Platinum exhibits essential characteristics for enhancing electrochemical processes, but the use of electrodes made entirely of Pt is not cost-effective. A more affordable alternative is electrodepositing Pt black on accessible metallic surfaces, such as brass, to ensure that the electrodes are both resistant to corrosive environments and possess catalytic capabilities. Pourbaix and kinetic analyses were performed to establish the optimal potential and current conditions for electrodepositing Pt black on brass utilizing a Pb-free Pt solution. The Pourbaix analysis indicated that Pt electrodeposition is achieved from the PtCl6− ionic species and occurs before hydrogen evolution. Kinetic studies further revealed that Pt black nanoscale deposition on a brass surface requires mechanical surface treatment and electrochemical polishing, followed by metallic Pt electrodeposition under potentiostatic control at −295 mV vs. SCE. Subsequent Pt black deposition was achieved under galvanostatic control at −500 A cm−2. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) confirmed the formation of nanostructures of metallic Pt and Pt black on brass, with the latter presenting a larger surface area to enhance the active sites for catalysis in electrochemical processes.